Frontiers in Growth Regimes Research II: Country Cases. Editorial to the special issue - Ümit Akçay; Eckhard Hein; Benjamin Jungmann; Ryan Woodgate (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
"Frontiers in Growth Regimes Research II: Country Cases" published on 05 Apr 2024 by Edward Elgar Publishing Ltd.
Keywords: 330